Kod Etika Wartawan Malaysia 2024 Daripada Perspektif Maqasid Syariah - Nur Kamilah Kamaruddin; Nik Nurul Akmal Ab Alim; Nor Azrina @ Nor Azura Ab Rahman; Siti Nor Azimah Sabaruddin (Universiti Sains Islam Malaysia, 2025)
Journal of Fatwa Management and Research, Volume 30 Issue 1 Page (142–173)